2016
DOI: 10.1080/12269328.2016.1162113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic inter-relationships among tourism, economic growth and energy consumption in India

Abstract: This study attempts to explore the dynamic causal and inter-relationships among tourism, economic growth and energy consumption in India. This study covers the annual data from 1971 to 2012. This study applies the cointegration and generalised variance decomposition methods to verify the relationship. The bounds testing approach to cointegration and the Gregory-Hansen test for cointegration with structural break consistently reveal that energy consumption, tourism and economic growth in India are cointegrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 69 publications
(84 reference statements)
3
44
1
Order By: Relevance
“…Support for the feedback hypothesis is also observed in the relationship between renewable energy consumption and tourism development, implying that these factors rely on each other for advancement. A causal link between tourism development and economic growth is found, which supports the tourism-led growth hypothesis (Lee & Brahmasrene, 2013;Tang et al, 2016) (Ajmi, Apergis, & Montasser, 2015). The results support our notion that the causal relationships are not the same across the countries in the panel.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Support for the feedback hypothesis is also observed in the relationship between renewable energy consumption and tourism development, implying that these factors rely on each other for advancement. A causal link between tourism development and economic growth is found, which supports the tourism-led growth hypothesis (Lee & Brahmasrene, 2013;Tang et al, 2016) (Ajmi, Apergis, & Montasser, 2015). The results support our notion that the causal relationships are not the same across the countries in the panel.…”
Section: Discussionsupporting
confidence: 81%
“…More recently, Tang, Tiwari, and Shahbaz (2016) examined the causal relationship between tourism, growth, and energy variables and found evidence supporting the tourism-led growth hypothesis in India.…”
Section: Introductionmentioning
confidence: 99%
“…Also, on a similar study on Cyprus, Katircioglu et al ( 2014 ) reveal that in the long run, international tourist arrivals have a positive inelastic relationship with the level of energy consumption. Likewise, from a trivariate analysis, Tang et al ( 2016 ) showed energy consumption is driven by tourism in the long run in India. Işik et al ( 2017b ) find a bidirectional causal relationship between tourist arrivals and energy consumption in ten most visited countries in the world.…”
Section: Literature Review and Stylized Factsmentioning
confidence: 99%
“…Following studies Lee and Brahmasrene (2013), Tiwari et al (2013), Leon et al (2014), and Tang et al (2016) that focus on the link of tourism-energy-growth nexus, this study uses the following models where economic growth (Y) is the dependent variable, and energy consumption (EGY) and tourism are the independent variables. We used E-Views 8 econometric software for the estimations.…”
Section: Model and Datamentioning
confidence: 99%